Uji Komposisi Biochar Sekam Padi Selama Penyimpanan terhadap Viabilitas Isolat RTCR01 sebagai Carrier Pupuk Hayati di Kabupaten Timor Tengah Utara - Fallo, Gergonius; Usfinit, Yohana Fatmawati; Pardosi, Lukas (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Carrier material is one of the significant factors for the success of using biofertilizer since it plays an important role in maintaining microbial viability of which contained in it. This study aimed to find out the composition of carrier materials of rice husk biochar for the viability of isolate RTCR01. This study was conducted at Agriculture Laboratory of Timor University. It started out with isolate RTCR01 recultivation, culture making for nutrient broth media, rice husk biochar making, and injection of 10 ml culture of isolate RTCR01 on various compositions of carrier materials of rice husk biochar. Viability of isolate RTCR01 was observed every week using plate count method on PCA media, while data analysis of the effect of rice husk biochar on the bacterial viability used descriptive analysis. Results of this study suggested that the composition that showed the highest viability of isolate RTCR01 was on the first week of storage namely C3: biochar of 500 gr + tapioca flour of 250 gr + cow dung of 250 gr, meanwhile the viability at the end of storage period on the 8th week included C1: biochar of 500 gr. Observation result suggested that all treatments using the composition of rice husk biochar can maintain bacterial viability during the storage period for 8 weeks.